Pengaruh senam aerobic terhadap kebugaran jasmani ibu PKK - Anastasya, Anastasya; Jalil, Rasyidah; Saman, Saman; Kahar, Irsan; Hakim, Nurwahidin (Universitas Hamzanwadi, 2023)
The purpose of this study was to determine the effect of aerobic exercise on the physical fitness of PKK Saluinduk Village mothers. This study included a pre-experimental study with a one group pretest-posttest design. The population numbered 20 people while the sampling technique was carried out using the total sampling technique, namely the entire population was used as a sample, so that in this study the sample totaled 20 people who were treated with aerobic exercise and measured physical fitness before and after being treated with a multistage fitness test instrument (beep tests). Data analysis techniques using descriptive statistics with t-test. The results showed that the tcount value was greater than ttable (4.30266 > 1.99773) thus the t value obtained in this study was significant. So it was concluded that aerobic exercise had an influence on the physical fitness of PKK Saluinduk Village mothers.